2004
DOI: 10.1128/aac.48.4.1422-1425.2004
|View full text |Cite
|
Sign up to set email alerts
|

2′-Fluoro-2′-Deoxycytidine Inhibits Borna Disease Virus Replication and Spread

Abstract: Borna disease virus (BDV) causes neurological diseases in a variety of warm-blooded animal species, possibly including humans. To date, there is no effective treatment against BDV infection. Recently, we reported on the antiviral activity of 1-␤-D-arabinofuranosylcytosine (Ara-C). However, Ara-C's cytotoxic side effects are a major obstacle for its therapeutic use. Herein, we demonstrate that the nucleoside analog 2-fluoro-2-deoxycytidine (2-FdC) exhibits potent antiviral activity against BDV. Importantly, 2-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…is a nucleoside inhibitor used in anticancer drugs. It inhibits various RNA and DNA viruses in vitro, such as Borna virus (Bajramovic et al, 2004), Lassa virus (Welch et al, 2016), Crimean-Congo hemorrhagic fever virus (Welch et al, 2017), influenza virus (Kumaki et al, 2011), and herpesviruses (Wohlrab et al, 1985). Smee et al (2018) has shown the antiviral activity of 2 ′ -FdC against various bunyaviruses, such as La Crosse virus, Maporal virus, Punta Toro virus, Rift Valley fever virus, San Angelo virus, Heartland virus, and SFTSV.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…is a nucleoside inhibitor used in anticancer drugs. It inhibits various RNA and DNA viruses in vitro, such as Borna virus (Bajramovic et al, 2004), Lassa virus (Welch et al, 2016), Crimean-Congo hemorrhagic fever virus (Welch et al, 2017), influenza virus (Kumaki et al, 2011), and herpesviruses (Wohlrab et al, 1985). Smee et al (2018) has shown the antiviral activity of 2 ′ -FdC against various bunyaviruses, such as La Crosse virus, Maporal virus, Punta Toro virus, Rift Valley fever virus, San Angelo virus, Heartland virus, and SFTSV.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…However, its use is compromised by side effects. Some other antivirals have also been developed against BDV, but these trials have so far remained in the initial phase (Planz et al, 2001;Bajramovic et al, 2004;Volmer et al, 2005;Qian et al, 2010).…”
Section: Treatment and Prevention Of Bdmentioning
confidence: 99%
“…It is noteworthy that 2′-fluoro-2′-deoxycytosine (FdC) ( 6-6a) was found to be a potent anti-HCV agent with EC 90 value of 5 μM, which is more potent than ribavirin, an FDA approved anti-HCV drug [18]. FdC ( 6-6a) also exhibits potent antiviral activity against Borna disease virus (BDV) [19]. …”
Section: Synthesis Of Carbohydrate Fluorinated Nucleosidesmentioning
confidence: 99%